Muscle Micromorphology and Histomorphometry of Sumba Ongole Cattle (Bos indicus) - Chandraone P. Kefi Amtiran; Filphin A. Amalo; Inggrid T. Maha; Heny Nitbani (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
This study aims to knowing the micromorphology and histomorphometry of the sumba ongole cattle muscles. The sample used was 6 muscle samples consisted of the longissimus dorsi and bicep femoris muscles taken from three sumba ongole cattle slaughtered at the West Sumba slaughterhouse. Muscle tissue was fixed using 10% formalin and made histological preparations and hematoxylin-eosin (HE) staining. Histological preparations were observed using a light microscope with objective magnifications of 4, 10, 40, and 100 times. The results showed that the muscle micromorphology in the transverse section consisted of many fascicles formed by muscle fibers with cell nuclei at the edges, connective tissue, and intramuscular fat. Muscles in longitudinal sections are formed by muscle fibers with light dark stripes and connective tissue. The muscle fibers diameter, fascicle diameter and thickness of the connective tissue in the bicep femoris muscle is higher than the longissimus dorsi muscle. In contrast, the number of muscle fibers per fascicle is higher in the longissimus dorsi muscle. Muscle histomorphometry are strongly influenced by anatomical location and function of the muscles, as well as the presence of intramuscular fat.